1992
DOI: 10.1055/s-2007-1003272
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Glycerylphosphorylcholine Administration Increases the GH Responses to GHRH of Young and Elderly Subjects

Abstract: Growth hormone (GH) secretion is decreased during aging in humans and in rodents. This decrease may be due to increased hypothalamic somatostatin release, which is inhibited by cholinergic agonists, or to decreased secretion of GHRH. Alpha-glyceryl-phosphorylcholine (alpha-GFC) is a putative acetylcholine precursor used in the treatment of cognitive disorders in the elderly. In order to learn what effect alpha-GFC had on GH secretion, GH-release hormone (GHRH) was given to young and old human volunteers, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
2
9
0
3
Order By: Relevance
“…GHRH is the hypothalamic hormone that triggers secretion of GH from the pituitary. The observation that both CDP-choline [49] and choline alphoscerate [50] improve the age-related decline in GH responsiveness to GHRH, further strengths the cholinergic activity of the compounds. The interference with mechanisms of GH release suggests that the two compounds may be also considered for other indications besides the most documented in cognitive domains.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…GHRH is the hypothalamic hormone that triggers secretion of GH from the pituitary. The observation that both CDP-choline [49] and choline alphoscerate [50] improve the age-related decline in GH responsiveness to GHRH, further strengths the cholinergic activity of the compounds. The interference with mechanisms of GH release suggests that the two compounds may be also considered for other indications besides the most documented in cognitive domains.…”
Section: Discussionmentioning
confidence: 83%
“…In clinical pharmacology settings they counter the amnesia induced by the cholinergic muscarinic receptor antagonist scopolamine [47,48]. Moreover, CDPcholine and choline alphoscerate counter the age-related decline of both growth hormone (GH) synthesis and release [49,50]. GH decline is associated with cognitive impairment occurring in the elderly [51] and cholinergic system is an important part of mechanisms regulating GH release stimulated by growth hormone-releasing hormone (GHRH) [52].…”
Section: Discussionmentioning
confidence: 99%
“…An increased of brain cholinergic tone by administration of choline alphoscerate was demonstrated by the clinical pharmacology study mentioned below [38]. Growth hormone (GH) secretion is decreased in aging.…”
Section: Pharmacokineticsmentioning
confidence: 92%
“…It can increase acetylcholine levels in motor units, 48,49 is essential in phospholipids, a major component of all biological membranes, 50 and is important in the release of human growth hormone. 51, 52 Infante 53 showed that GPC aided sarcoplasmic Ca 2þ transport, and Suchy et al 54 showed that cognitive degeneration was delayed with GPC supplementation. It was also shown that PC immunization reduces foam cells, which are products of inflammation.…”
Section: The Effect Of Grounding On Doms 269mentioning
confidence: 99%